The Tradition of ‘Balochi Chawat (Balochi Shoes)’ Manufacturing - Hussain, Mujahid; Baloch, Hamid Ali (sourcecoder, 2023)
Chawat (Balochi Shoes) manufacturing industry has been a popular industry in Balochistan from thousands of years. Balochi Chawats is manufactured with different styles in different parts of Balochistan, but the Prince Road Quetta is the biggest center for manufacturing of the Balochi Chawats, where millions of rupees are earned in a month. This industry has been the source of income of the local people from hundreds of years. The Balochi Chawats are exported to the different countries of the world by the shopkeepers during the Eid, events and marriage functions. Apart from this, the local people spend money to buy chawat during different occasions. So, this paper illustrates the manufacturing history of Chawat industry in Quetta, its importance in the Baloch society and inattentions of the govt. towards this industry.